2010
DOI: 10.1016/j.jvs.2009.08.097
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of thromboembolic events in surgical patients through the creation and implementation of a computerized risk assessment program

Abstract: The creation and implementation of a standardized DVT risk assessment program in the electronic medical record significantly increased use of pharmacological and mechanical DVT prophylaxis before surgery in a Veterans Affairs Medical Center setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 19 publications
1
31
0
1
Order By: Relevance
“…Several recent studies have shown significant reduction in VTE rates as a result of increasing prophylaxis utilization through implementing new protocols and guidelines. [16][17][18] As obesity is still associated with worsening overall postoperative morbidity, 19,20 this supports our hypothesis that DVT rates are similar as a result of increased VTE prophylaxis.…”
Section: Commentssupporting
confidence: 62%
“…Several recent studies have shown significant reduction in VTE rates as a result of increasing prophylaxis utilization through implementing new protocols and guidelines. [16][17][18] As obesity is still associated with worsening overall postoperative morbidity, 19,20 this supports our hypothesis that DVT rates are similar as a result of increased VTE prophylaxis.…”
Section: Commentssupporting
confidence: 62%
“…Second, we were able to create our order set within a commercial EHR used by more than 300 academic and community healthcare institutions in and outside the U.S.; thus, our intervention can be utilized by many other institutions either using the same or a similar EHR. Third, we were able to reach all hospitalized populations across multiple hospitals in an academic health care system, instead of select populations [8,11,12] or a single hospital [17] as investigated in many other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many methods to improve VTE prophylaxis in the hospital setting have been studied, including the use of computerized clinical decision support (CDS) interventions [6]. However, many of the CDS interventions studied were limited in that they either used noncommercial homegrown electronic health records (EHR) [7-13], pop-up alerts to remind providers when patients with VTE risk factors were not on prophylaxis [7-11,13-16], or targeted select populations [8,11,12] or individual hospitals [17]. These limitations could impact the generalizability of the studies’ findings across multi-hospital systems, particularly given the ubiquitous nature of pop-up alerts and the associated alert fatigue [18], challenges associated with translating the functionality of a homegrown EHR into a commercial one, and obstacles associated with implementing change across multiple institutions.…”
Section: Introductionmentioning
confidence: 99%
“…There are data supporting the utilization of clinical decision support tools (CDST) within the EHR and their impact on VTE prophylaxis compliance. [5][6][7] Haut and colleagues conducted a study to examine documentation and compliance to guidelines in a trauma population before and after a mandatory risk factor stratification tool and orderset. 6 They found that both documentation and compliance increased following implementation (3% vs 97.8% and 66.2% vs 84.4%, respectively; P < .001).…”
Section: Discussionmentioning
confidence: 99%